STUDI DESKRIPTIF IMPLEMENTASI KEBIJAKAN PEMBANGUNAN INFRASTRUKTUR JALAN DI KABUPATEN SEMARANG TAHUN 2013 - fathorikh, fatnan; SANTOSA, EDI; DZUNUWANUS, GHULAM (Journal of Politic and Government Studies, 2016)
ABSTRACTPolicy implementation in providing regional infrastucture towardinvestment and economic drivers is a policy that set by government into SemarangDistrict Regulation No. 7 of 2011 on the Semarang District Medium TermDevelopment Plan Year 2010-2015 by considering conditions and problems andneeds faced by communities as well as by considering strategic and potentialfactors of the community and local government.This study is a qualitative study with main purpose to describe aboutpolicy implementation in providing regional infrastuctures toward investment andeconomic drivers. It also explains inhibiting factor and the government’s strategyto solve problems. Data collection techniques in this study are using observationmethods, interviews and documentary study.The study concluded that policy implementation in providing regionalinfrastuctures toward investment and economic drivers has run optimally in itsimplementation. Semarang District Public Works Department and its Agencies /Related SKPD have made the development and roads aftercare service in thedistrict of Semarang properly and according to procedure. Moreover,socialization also has been done with coordination meeting between SKPD ordirectly to the public by village authoritiesHowever, there are some drawbacks such as lack of resources this islimitation on budgetary funds which resulted in burden for next financial year.Semarang District Government should attempte to actively communicate withcentral government to disburse APBN fund for infrastructure development in theSemarang Regency.Keywords: Implementations, Infrastructures, Semarang Regency, Policies.